Synthesis and Characterization of the Hexafluoridomolybdates(V) A[MoF6] (A = Li – Cs). Issue 19 (16th April 2020) - Stene, Riane E.; Scheibe, Benjamin; Petry, Winfried; Kraus, Florian
Abstract : The hexafluoridomolybdates(V), A [MoF6 ] ( A = Li – Cs), were synthesized by reacting molybdenum pentafluoride (MoF5 ) with the alkali metal fluorides in anhydrous hydrogen fluoride (aHF) solution. Single crystals of A [MoF6 ] ( A = Li, Na, Rb, Cs) were grown from solution and analyzed by single‐crystal X‐ray diffraction. The vibrational spectrum of each salt is reported in detail and compared to previously reported spectra. During analysis of the cubic modification of Na[MoF6 ] it was noticed that a phase transition occurs around 228 K. Some details regarding this phase transition are discussed. Attempts to determine the structure of the low‐temperature phase of Na[MoF6 ] lead to the observation of the Na[MoF6 ]· 2HF solvate. Additionally, in an attempt to synthesize Na[MoF7 ] by the oxidation of Na[MoF6 ] in chlorine trifluoride (ClF3 ), a tetragonal modification of Na[MoF6 ] was observed. The crystal structures of the Na[MoF6 ]· 2HF solvate and tetragonal modification of Na[MoF6 ] are also discussed in detail. Abstract : The hexafluoridomolybdates(V), A [MoF6 ] ( A = Li – Cs) were synthesized and characterized by IR and Raman spectroscopy. The crystal structures of A [MoF6 ] ( A = Li, Na, Rb, Cs) determined by single‐crystal X‐ray diffraction are discussed in detail. A new, tetragonal modification of Na[MoF6 ] was observed along with the Na[MoF6 ]· 2HF solvate. The crystal structures of both compounds are also fully discussed.